2011
DOI: 10.1108/17538391111186564
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of e‐banking readiness in Jordan

Abstract: Purpose -The purpose of this paper is to propose and validate a framework that can be used for assessing the level of banks' readiness for providing e-banking services in Jordan. Design/methodology/approach -A questionnaire-based data-gathering technique, descriptive, and analytical analyses are used. Findings -This study has used three constructs to propose a framework that can assess e-banking readiness: perceptions of bankers, perceptions of customers, and IT infrastructure in banks. However, there is evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…However, the implementation of Telebanking will not be profitable unless customers adopt this technology (Dwivedi et al, 2006;Meuter et al, 2005). By the same token, acceptance of Telebanking by Jordanian customers is still low as are other SST banking channels: Internet banking and Mobile banking (Alalwan et al, 2014;Alafeef et al, 2012;Al-Majali, 2011;Al-Rfou, 2013;Al-Smadi, 2012;Awwad and Ghadi, 2010;Salhieh et al, 2011). For instance, based on a recent survey involving 40 bank staff who are specialists in the online transactions' department in 16 Jordanian commercial banks, Al-Rfou (2013) reported that less than 20% of the total banking customers in Jordan have used the online banking services.…”
Section: Introductionmentioning
confidence: 99%
“…However, the implementation of Telebanking will not be profitable unless customers adopt this technology (Dwivedi et al, 2006;Meuter et al, 2005). By the same token, acceptance of Telebanking by Jordanian customers is still low as are other SST banking channels: Internet banking and Mobile banking (Alalwan et al, 2014;Alafeef et al, 2012;Al-Majali, 2011;Al-Rfou, 2013;Al-Smadi, 2012;Awwad and Ghadi, 2010;Salhieh et al, 2011). For instance, based on a recent survey involving 40 bank staff who are specialists in the online transactions' department in 16 Jordanian commercial banks, Al-Rfou (2013) reported that less than 20% of the total banking customers in Jordan have used the online banking services.…”
Section: Introductionmentioning
confidence: 99%
“…This is important because the successful implementation of information systems is dependent on the extent to which such a system is used and eventually adapted by the potential users [10]. Therefore, there is a need for banks to assess their readiness to offer e-banking services to their clients [11]. It is important to understand the factors influencing cus-tomers to use bank services and how they can be attracted to use both the online and offline services.…”
mentioning
confidence: 99%
“…In studies conducted to examine the main factors predicting the Jordanian customers' intention and adoption of telebanking, Al-Rfou (2013) emphasizes the use of e-banking from the viewpoint of electronic services staff and the phase which impacts it, such as the acceptance of the system by clients, and how clients can be persuaded to make the most of the financial activity by using e-banking. Salhieh et al (2011) proposed and validated a framework that can be used for assessing the level of banks' readiness to provide e-banking services in Jordan. Al-Somali et al (2008) examined the factors that encourage customers to adopt online banking in Saudi Arabia.…”
Section: The Most Influential Factors In the Developing And Developedmentioning
confidence: 99%